Community pharmacy-delivered interventions for public health priorities: a systematic review of interventions for alcohol reduction, smoking cessation and weight management, including meta-analysis for smoking cessation. Issue 2 (29th February 2016) - Brown, Tamara J; Todd, Adam; O'Malley, Claire; Moore, Helen J; Husband, Andrew K; Bambra, Clare; Kasim, Adetayo; Sniehotta, Falko F; Steed, Liz; Smith, Sarah; Nield, Lucie; Summerbell, Carolyn D
Abstract : Objectives: To systematically review the effectiveness of community pharmacy-delivered interventions for alcohol reduction, smoking cessation and weight management. Design: Systematic review and meta-analyses. 10 electronic databases were searched from inception to May 2014. Eligibility criteria for selecting studies: Study design : randomised and non-randomised controlled trials; controlled before/after studies, interrupted times series. Intervention : any relevant intervention set in a community pharmacy, delivered by the pharmacy team. No restrictions on duration, country, age, or language. Results: 19 studies were included: 2 alcohol reduction, 12 smoking cessation and 5 weight management. Study quality rating: 6 'strong', 4 'moderate' and 9 'weak'. 8 studies were conducted in the UK, 4 in the USA, 2 in Australia, 1 each in 5 other countries. Evidence from 2 alcohol-reduction interventions was limited. Behavioural support and/or nicotine replacement therapy are effective and cost-effective for smoking cessation: pooled OR was 2.56 (95% CI 1.45 to 4.53) for active intervention vs usual care. Pharmacy-based interventions produced similar weight loss compared with active interventions in other primary care settings; however, weight loss was not sustained longer term in a range of primary care and commercial settings compared with control. Pharmacy-based weight management interventions have similar provider costs to those delivered in other primary care settings, which are greater than those delivered by commercial organisations. Very few studies explored if and how sociodemographic or socioeconomic variables moderated intervention effects. Insufficient information was available to examine relationships between effectiveness and behaviour change strategies, implementation factors, or organisation and delivery of interventions. Conclusions: Community pharmacy-delivered interventions are effective for smoking cessation, and demonstrate that the pharmacy is a feasible option for weight management interventions. Given the potential reach, effectiveness and associated costs of these interventions, commissioners should consider using community pharmacies to help deliver public health services.